An Analysis of Factors Affecting Medication Adherence and Disease Recurrence Rate in Asthma Patients - Hartanti, Rita Dwi; Akbar, Syaeful; Aktifah, Nurul; Natalya, Wiwiek (Media Keperawatan Indonesia, 2025)
Medication adherence and disease recurrence rates in asthma patients greatly affect the patient's quality of life. Knowledge of factors that influence medication adherence and disease recurrence rates can significantly impact physical health and, consequently, patient quality of life. This study aims to identify factors that influence medication adherence and disease recurrence rates in patients with asthma. This study employed a descriptive analytical method with a multiple linear design. Data collection was conducted from July 5 to 30, 2025. Assessment of medication adherence was done by the Medication Adherence Report Scale (MARS) questionnaire and evaluation of disease recurrence rates using asthma recurrence questionnaires. The results of data analysis using multiple linear tests showed that factors influencing medication adherence in asthma patients were gender (29.35%), education (14.48%), and the triggers for relapse (21.34%). Factors that influence the rate of disease recurrence in asthma patients are education (17.5%), occupation (14.2%), and the triggers for relapse (76.1%). Based on the study's results, several factors similar to those influencing medication adherence and disease recurrence rates were identified, including education and the triggers for relapse.